2009
DOI: 10.1007/978-3-642-02927-1_52
|View full text |Cite
|
Sign up to set email alerts
|

General Scheme for Perfect Quantum Network Coding with Free Classical Communication

Abstract: This paper considers the problem of efficiently transmitting quantum states through a network. It has been known for some time that without additional assumptions it is impossible to achieve this task perfectly in general -indeed, it is impossible even for the simple butterfly network. As additional resource we allow free classical communication between any pair of network nodes. It is shown that perfect quantum network coding is achievable in this model whenever classical network coding is possible over the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
110
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(110 citation statements)
references
References 18 publications
0
110
0
Order By: Relevance
“…The proposed quantum transmission attains the optimal transmission capacity under the assumption of restricted maximum-flow; in this respect, it is superior to other proposed approaches9101112131415. Unlike quantum k -pair tasks with enlarged linear encodings1314 or nonlinear encodings15, our encoding is linear and is not completed in an enlarged space. And classical channels are assumed to exist only for the common quantum channels and not all quantum channels15.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The proposed quantum transmission attains the optimal transmission capacity under the assumption of restricted maximum-flow; in this respect, it is superior to other proposed approaches9101112131415. Unlike quantum k -pair tasks with enlarged linear encodings1314 or nonlinear encodings15, our encoding is linear and is not completed in an enlarged space. And classical channels are assumed to exist only for the common quantum channels and not all quantum channels15.…”
Section: Discussionmentioning
confidence: 91%
“…And classical channels are assumed to exist only for the common quantum channels and not all quantum channels15. Moreover, the new scheme extends the solvability of the quantum k -pair problem, and is more general than previous schemes131415 which depend on the solvability of the classical k -pair problem. One typical example is presented in the Figure 1(c); this example is unsolvable525354 in terms of the classical 2-pair problem using network coding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is expected that network coding also allows the same resolution in a quantum network. In recent years, a number of researchers have studied quantum network coding [21][22][23][24][25][26][27] . However, all of these studies presuppose the use of pure states and perfect local gates.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], it is shown that perfect quantum 2-pair communication over the butterfly network is possible if we add two maximally entangled qubits between the two inputs and allow each channel to use either one qubit or two bits of communication. If classical communications are not restricted and only quantum communications are restricted, it is shown that any quantum k-pair problem has a solution if the corresponding classical k-pair problem has a solution [4] for the network. …”
mentioning
confidence: 99%